Strategi Kualitas Bagian Front Office Dalam Meningkatkan Pelayanan Di Dinas Koperasi Dan UKM DIY - Nurmufida, Lely; Hartadi, Agung (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2024)
This research aims to determine the quality strategy for front office services at the Dinas Koperasi Dan UKM DIY. The research subjects were employees at the service. data collection techniques using observation, documentation and interviews. while data analysis using SWOT analysis and the Miles and Huberman technique